CLINICAL PRESENTATION OF LEFT VENTRICULAR NONCOMPACTION DIAGNOSED IN ADULTS - Kacper Curzytek; Marcelina Podleśna; Karol Chromiak; Aleksandra Stępień; Kacper Bączek; Kacper Bluczak; Marta Krzyżanowska; Anna Drużdżel; Zuzanna Parfienowicz; Katarzyna Czechowicz (International Journal of Innovative Technologies in Social Science, 2026)
Left ventricular noncompaction (LVNC) is a rare, morphologically and genetically heterogeneous form of cardiomyopathy, the pathogenesis, classification, and clinical significance of which remain subjects of ongoing debate. The aim of this review is to present the current state of knowledge regarding the classification, pathophysiology, diagnostics, genetic determinants, clinical presentation, and therapeutic management of LVNC. The European Society of Cardiology (ESC) classifies LVNC as an unclassified cardiomyopathy, whereas the American Heart Association (AHA) considers it a genetically determined cardiac disorder. The characteristic morphology arises from abnormal compaction of the left ventricular trabeculae during embryogenesis, although an acquired or adaptive origin of these changes is also possible. Diagnostic evaluation relies primarily on echocardiography and cardiac magnetic resonance imaging; however, the lack of uniform morphological criteria contributes to both overdiagnosis and underdiagnosis. From a genetic perspective, sarcomeric gene mutations predominate and are associated with more severe clinical outcomes. Clinical manifestations include heart failure, arrhythmias, and thromboembolic complications, with reduced left ventricular ejection fraction being the principal prognostic factor. Therapeutic management follows general heart failure treatment strategies, thromboembolism prevention, and implantation of cardiac devices; in advanced cases, heart transplantation or mechanical circulatory support may be considered. An integrated diagnostic approach and the MOGE(S) classification system may serve as a foundation for future standardization.